"Turn-on" fluorescence sensor for vitamin B1 based on cyanostilbene macrocycle. (November 2022) - Chen, Jiaojiao; Huang, Xinyao; Tang, Hui; Guo, Hongyu; Yang, Fafu
Abstract: Although some detecting methods for vitamin B1 had been reported, the rapid, simple and on-site detection for vitamin B1 is extremely anticipated. In this research, a novel organic fluorescence sensor for vitamin B1 was developed for rapid and on-site detection of vitamin B1. A crown-ether cyanostilbene macrocycle was synthesized by Schiff-base "1 + 1" condensation. It displayed the "turn-on" green fluorescence on selective and sensitive detection of vitamin B1 among various guests in aqueous media. The detection limit was 7.8 × 10 −7 M. The 1:1 stoichiometric binding mechanism was elucidated by fluorescence Jobs' plot, MS spectra, FT-IR spectra and 1 H NMR spectra. This sensing ability for vitamin B1 was successfully applied in test paper and on-site detecting vitamin B1 in actual samples of peanut and vitamin B1 pills, suggesting the good application prospect in the detection of vitamin B1 in food and tablets in complicated environments. Graphical abstract: Image 1 Highlights: The novel organic fluorescent sensor for vitamin B1 was reported. It exhibited the strong "turn-on" green fluorescence for vitamin B1 in aqueous media. It displayed the high sensing selectivity and sensitivity for vitamin B1. The detecting limitation of sensor for vitamin B1 was 7.8 × 10 −7 M. It was successfully used for sensing vitamin B1 in real vegetable, food and tablets.